Answer :

We know that (x – 1) will be the factor of the polynomial if by substituting x = 1 in polynomial we get the zero remainder

∴ by putting x = 1 in x^{3} – x^{2} – (2 + √3)x + √3, we get -

1^{3} – 1 – (2 + √3)1 + √3 = 1 – 1 – 2 – √ 3 + √ 3

= – 2≠0

⇒ (x – 1) is not a factor of x^{3} – x^{2} – (2 + √3)x + √3

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation